2011
DOI: 10.1524/zpch.2012.0173
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Structure Explain the Viscometric Behavior of AOT Microemulsions at Low Water/AOT Molar Ratios

Abstract: The viscosity of AOT/water/decane water-in-oil microemulsions exhibits a well-known maximum as a function of water/AOT molar ratio, which is usually attributed to increased attractions among nearly spherical droplets. The maximum can be removed by adding salt or by changing the oil to CCl 4 . Systematic small-angle X-ray scattering (SAXS) measurements have been used to monitor the structure of the microemulsion droplets in the composition regime where the maximum appears. On increasing the droplet concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 66 publications
(128 reference statements)
1
15
0
Order By: Relevance
“…The fittings of the correlation functions for the pure microemulsion show that the size distribution of the particles is not changing when changing the droplet mass fraction and that it is rather narrow (β = 0.98), Figure 2. The value of β for mixed polymer and microemulsion is slightly lower than for pure microemulsion, which demonstrates that either the polydispersity or cooperativity [20] of the mixed system is increased by the addition of the polymer (Figure 2). In addition Figure 2 illustrates that is decreasing by increasing the mass fraction of droplet and for the lowest droplet mass fraction, the value is virtually not affected the addition of polymer.…”
Section:  mentioning
confidence: 97%
See 1 more Smart Citation
“…The fittings of the correlation functions for the pure microemulsion show that the size distribution of the particles is not changing when changing the droplet mass fraction and that it is rather narrow (β = 0.98), Figure 2. The value of β for mixed polymer and microemulsion is slightly lower than for pure microemulsion, which demonstrates that either the polydispersity or cooperativity [20] of the mixed system is increased by the addition of the polymer (Figure 2). In addition Figure 2 illustrates that is decreasing by increasing the mass fraction of droplet and for the lowest droplet mass fraction, the value is virtually not affected the addition of polymer.…”
Section:  mentioning
confidence: 97%
“…Small-angle X-ray scattering (SAXS) measurements were performed using the pinhole SAXS instrument at the Aarhus University, [20]. The instrument consists of an X-ray camera (NanoSTAR, Bruker AXS) with a rotating anode X-ray (Cu Ka radiation) source, cross-coupled Göbel mirrors, collimation using three pinholes, an evacuated beam path, and a 2D position-sensitive gas detector (HiSTAR).…”
Section: Small-angle X-ray Scatteringmentioning
confidence: 99%
“…This study is an attempt to understand the collective diffusion coefficient of AOT/ H 2 O/Decane microemulsion at low water concentration X = 6.7 construct with photon correlation spectroscopy. Our previous work on AOT microemulsion at 6.7 shows a spherical to cylindrical transition [9]. In the present work, we studied the behavior of the collective diffusion coefficient (D c ) at the fix water to oil ratio (X = 6.7) and low mass fraction, by means of photon correlation spectroscopy and SAXS techniques.…”
Section: Introductionmentioning
confidence: 94%
“…The aqueous part of microemulsion is usually water or a solution of water with salts. The dynamic properties of microemulsions and colloidal systems are studied by photon correlation spectroscopy (PCS) [6][7][8] and the structure of AOT microemulsions are well investigated at water to the surfactant molar ration 6.7 [9]. A study shown, for AOT/H 2 O/ Decane microemulsion, at the low droplet mass fractions (0.01< m f <0.1 and molar ratio 40) the collective diffusion coefficient has a linear behavior as function of the mass fraction [10].…”
Section: Introductionmentioning
confidence: 99%
“…Reproduced by permission of The Royal Society of Chemistry tendency to form elliptical or cylindrical shape as a consequence of a change in the hydrated volume of the counter ion Na + and the influence of the oil on the droplet structure [50]. This might be the reason for some interesting properties of water/AOT microemulsions in the droplet phase like the large values of the viscosity [50] or the strength of the dielectric relaxations of the AOT shell in this ω-regime [51,52] as discussed in Sect. 2.3.2.…”
Section: Critical Behaviour-aggregation In the Droplet Phasementioning
confidence: 99%